Leveduras vivas em dietas para bovinos em semiconfinamento - Oliveira, Sullyvan Silva (2020)
The objective of this work was to evaluate the levels of yeast Saccharomyces cerevisiae strain KA500 for beef steers supplemented in 2.0% of body weight with a semi-confinement diet. Five (5) rumen-cannulated crossbred steers with an average body weight of 300 kg were randomly distributed in a 5x5 Latin square design and kept in individual paddocks of Urochloa brizantha. Animal supplementation consisted of 20% protein-mineral-vitamin pellets and 80% whole grain corn. Yeast was included in five levels: 0g, 5g, 10g, 15g and 20g. Supplement, crude protein and starch intakes had a quadratic effect (P>0.05), while dry matter, crude protein, NDF and starch digestibility had a linear effect (P>0.05). The different levels of live yeast did not show significant effects (P>0.05) for pH and ammonia nitrogen, but the production of propionate and butyrate showed quadratic effects (P>0.05). The treatments showed a quadratic effect (P>0.05) in the balance of o-consumption and fecal-N, while the data for N-retained, N urine and N-absorbed showed linear effects in response to the treatments. However, the offer of different levels of yeast to the animals showed a quadratic effect on supplement intake, DM, OM, CP and starch, for SCFA propionate and butyrate and on N-consumed and N-stool. And linear effect on the digestibility of DM, CP, NDF and starch, on the N balance the linear effect was found and on N-urine, N-retained and N-absorbed. Therefore, live yeasts should be potentially explored, however, the ideal would be studies that could explain their physiological mechanisms in the rumen and the requirements of microorganisms, so that it can facilitate the manipulation of ruminal microorganisms in animals subjected to different levels of yeast.